IDENTIFIKASI KEBUTUHAN PEMBIAYAAN SYARIAH PETERNAK LEMBU DI DELI SERDANG - Marlya Fatira AK; Anriza Witi Nasution; Tuti Kurnia (Asy-Syari'ah, 2020)
Abstract: This research identifies the needs of cattle breeders for Islamic financing for cattle business development to provide solutions to problems faced by breeders in Deli Serdang Regency, North Sumatra, especially in obtaining access to capital through Islamic financial institutions. The condition of the breeders included in the non-bankable criteria and did not have the 5 C criteria (character, capacity, collateral, capital, and conditions of economic), which are the main requirements for distribution of financing. One way to provide a solution to this problem is by providing easy access for farmers to obtain financing from LKMS with the most appropriate financing schemes and models for farmer business activities. In order to reach this stage, it is necessary to identify the needs of breeders. The research method used is a qualitative approach. Data were collected based on primary sources in the form of interviews with breeders, LKMS around Deli Serdang Regency. The results showed the main needs (needs) of breeders in managing their livestock business to be successful where the availability of capital during the maintenance period, the need for knowledge and skills in processing potential waste from livestock manure to become business and additional income from livestock management, the availability of routine health assistants. Conduct visits to help and provide counseling and control the health of livestock. The Islamic financing model for cattle breeders shows very promising business potential and opportunities for both parties of Islamic cooperatives and cattle breeders. The welfare opportunities formed in a multiplier manner from the sharia financing model for cattle breeders and sharia cooperatives based on investment with a yield within 42 months reach an equivalent rate of 72.5%.